Special features of the studies of deep electrical conductivity of the Moon and the Earth (once more on toroidal mode of natural magnetic field) - I.I. Rokityanskiy; A.V. Tereshyn (Геофизический журнал, 2020)
Studies of the deep electrical conductivity of the Earth and the Moon are carried out by measuring and analyzing the natural electromagnetic (EM) fields excited by the solar wind, introducing an electric field of the order of 2 mV/m applied to the boundaries of the Earth’s magnetosphere or directly to the surface of the Moon. For a concentrically layered sphere with electrical conductivity σ = σ (r), the EM fields can be represented as the sum of two modes: electric with a toroidal magnetic field and magnetic with a poloidal magnetic field. Each of the modes is associated with electrical conductivity by different ratios/formulas and is characterized by different possibilities for studying the electrical conductivity inside a celestial body. It is generally accepted that currents from the boundary of the Earth’s magnetosphere descend along the geomagnetic field lines to the ionosphere, but do not reach the Earth due to the very high resistance of near-the-surface air layer (up to 1014 Ohm · m) and only poloidal fields of the magnetic mode are induced in the solid Earth. A review of the data on the global electric circuit shows that vertical currents penetrate from the atmosphere into the Earth and the electric mode is not equal to zero. Vertical currents are characterized by strong spatio-temporal variability. Separation of the modes from observation data was not carried out. On the Moon, the high-resistance layer is the lithosphere with regolith and breccias on its surface with a resistivity of 107―1012 Ohm · m. Spatial inhomogeneities of the Moon interior are considered and a conclusion is made about their multitude and intensity. Based on the analysis of the spatial distribution of tidal and tectonic moonquakes, it was suggested that they trace quasi-vertical structures like a plume. The results of observations of volcanism and transient lunar phenomena, obtained in recent years by orbital missions with high-resolution equipment, indicate an intense degassing of the moon. All this allows us to conclude that in the Moon there are quasi-vertical conductors supporting an electric mode. Proposals for the optimization of new studies of the electrical conductivity of the moon are substantiated and formulated. Deep studies of electrical conductivity are based on a theoretical model of the magnetic mode, the existence of the electrical mode is neglected, and it falls into unidentified noise, which by means of coherent analysis and multi-stage processing is largely eliminated and the conductivity models more or less correctly describe the real geoelectric structure of the Earth, but with probable systematic errors. Separation and study of the electric mode should be considered as an additional channel of information in EM studies of planets.